(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2025)
Timber has been used in traditional Indonesia short-span roof structure. This short span timber structure still depended on the maximum length and thickness of the timber. Despite the introduction of the trusses system, timber constructions are still limited to short span roofs. Steel and concrete are still more popular to be used as long span roof structure material. This phenomenon was also shown in mosque roof structure development. The timber roof structure was replaced by steel and concrete long span roof, especially in form of dome structure. This paper presents the complexity of design to construction process of Nurul Hasanah Aceh Mosque in Palu City which pioneers the long-span single-layer folded grid timber roof structure in Indonesia. This article discusses design exploration of the mosque which showed the inseparable structural, construction, and architectural aspect in design process. The construction could serve as milestone for the development of long-span timber roof construction in Indonesia. This article also recommends several technical and computational improvement to further develop complex long-span timber structures in Indonesia.